Educational Communication of Prospective Teachers as a Reinforcement of the Integration of Mathematics and Islamic Education - Afifah Nurwahidah; Haniyah Shaffina Alfath; Lukmanul Akhsani (Yayasan Rahmat Islamiyah, 2026)
This study aims to investigate the communication processes employed by prospective teachers when integrating Islamic values into mathematics education, identifying effective tactics, patterns, challenges, and supporting factors to address gaps in prior research that focused mainly on student outcomes rather than teacher dynamics. The methodology involves a qualitative approach through systematic content analysis of academic journals, books, and relevant documents published between 2015 and 2025, sourced from databases such as Google Scholar and Garuda using targeted keywords like